2007
DOI: 10.1099/mic.0.2006/005405-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of a new fish-virulent Vibrio vulnificus serovar that lacks potential to infect humans

Abstract: Vibrio vulnificus is a bacterial species that is virulent for humans and fish. Human isolates are classified into biotypes 1 and 3 (BT1 and BT3) and fish isolates into biotype 2 (BT2). However, a few human infections caused by BT2 isolates have been reported worldwide (zoonosis). These BT2 human isolates belong to serovar E (SerE), which is also present in diseased fish. The aim of the present work was to characterize a new BT2 serovar [serovar A (SerA)], which emerged in the European fish-farming industry in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Further, these DNA sequences were all located in the plasmids, suggesting that the virulence for eels could be conferred by a plasmid. In fact, previous studies had shown that all BT2 strains harbored one or more plasmids of high molecular weight (6,22,30).The purpose of this study was to investigate the role of plasmids in the virulence of BT2 V. vulnificus for eels. Toward this end, we determined and analyzed the nucleotide se-* Corresponding author.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Further, these DNA sequences were all located in the plasmids, suggesting that the virulence for eels could be conferred by a plasmid. In fact, previous studies had shown that all BT2 strains harbored one or more plasmids of high molecular weight (6,22,30).The purpose of this study was to investigate the role of plasmids in the virulence of BT2 V. vulnificus for eels. Toward this end, we determined and analyzed the nucleotide se-* Corresponding author.…”
mentioning
confidence: 99%
“…Further, these DNA sequences were all located in the plasmids, suggesting that the virulence for eels could be conferred by a plasmid. In fact, previous studies had shown that all BT2 strains harbored one or more plasmids of high molecular weight (6,22,30).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The RAPD method has been initially used to detect polymorphism in genetic mapping, taxonomy and phylogenetic studies and later in genotoxicity and carcinogenesis studies (Atienzar and Jha 2006;Fouz et al, 2007). In addition, the fact that the RAPD assay allows the visualization of a wide range of PCR products may explain why this assay is a preferred choice.…”
Section: Introductionmentioning
confidence: 99%